Is Ischemic Preconditioning Intervention Occlusion-Dependent to Enhance Resistance Exercise Performance?. Issue 10 (October 2021) - de Souza, Hiago L. R.; Arriel, Rhaí A.; Hohl, Rodrigo; da Mota, Gustavo R.; Marocolo, Moacir
Abstract : Abstract: de Souza, HLR, Arriel, RA, Hohl, R, da Mota, GR, and Marocolo, M. Is ischemic preconditioning intervention occlusion-dependent to enhance resistance exercise performance? J Strength Cond Res 35(10): 2706–2712, 2021—Ischemic preconditioning is a rising technique with potential to improve performance. Currently, its effects are still controversial, and a placebo effect seems to have a role. In this sense, this study evaluated the effect of high-pressure (HP) and low-pressure (LP) cuffing on resistance exercise performance during repeated 5-day intervention. Twenty healthy trained men (24.0 ± 4.4 years; 80.1 ± 12.2 kg; and 176.9 ± 6.6 cm) performed a 1 repetition maximum (1RM) test before interventions. Maximal isometric force test, number of repetitions (75% 1RM), total workload (sets × reps × load), fatigue index (FI) ([set 1 − set 3]/set 1 × 100), and perceived scales were assessed during knee extension preceded by HP (3 × 5-minute unilateral leg occlusion at 50 mm Hg above systolic blood pressure), LP (3 × 5-minute unilateral leg occlusion at 20 mm Hg), or control ([CON] 30-minute resting). The main effect of cuff intervention was significant for total workload ( F (1, 16) = 4.2, p = 0.03) after adjusting for baseline (analysis of covariance). Adjusted means (confidence interval) and effect sizes (ES) indicate that HP (1778 kg [1, 613–1944]; ES: 0.29) and LP (1761 kg [1, 590–1932]; ES: 0.34) significantly increased total workload compared with CON (1, 452 kg [1, 262–1, 643]; ES: 0.17). Finally, isometric force and FI were similar for all conditions (HP, LP, and CON) with no difference from baseline performance. In conclusion, the short-term (5-day) intervention of HP and LP cuffing increases the total workload. This effect in muscle endurance performance is nondependent of blood flow occlusion, since LP is not able to obstruct arterial blood flow. A likely motivational effect cannot be ruled out.